Collaborative Learning Techniques For Developing Critical Thinking Abilities - Maarita Maijatla; Prem Chandu; Cindy E. Hmelo-Silvester; Paul A. Kirscehnera; Sarah J. Howienta; John Swelleretand (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
Critical thinking skills are essential competencies in addressing the challenges posed by globalization and digitalization in the modern era. This study investigates the application of collaborative learning strategies to foster students' critical thinking abilities. Employing a qualitative research design, the study uses a case study methodology conducted in three middle schools in Helsinki, Finland. Data collection methods include in-depth interviews, participatory observations, and document analysis. The findings demonstrate that collaborative learning, rooted in social constructivism theory, plays a pivotal role in enhancing students' analytical, evaluative, and reflective capabilities. Additionally, the integration of technology, such as digital collaboration tools, has been shown to improve group dynamics and promote active participation among students. Nonetheless, the research highlights significant challenges, including students' reluctance to engage in group work and insufficient facilitation skills among educators. To address these issues, the study provides strategic recommendations, emphasizing the need for teacher training, effective use of technology, and structured learning frameworks. These insights aim to support educators and policymakers in developing effective educational initiatives that equip students with critical thinking skills for the demands of the contemporary era.